Balance Scorecard Approach to employee performance management in Tyre Company - Firdaus, Muhamad Azis; Ginanjar, Apik; Hasnin, Hannisa Rahmaniar (Goodwood Publishing, 2025)
Purpose: This research aims to analyze employee performance management strategies using the Balance Scorecard approach in a tire company. In this study, a qualitative descriptive method was used with primary and secondary data collection techniques. Research Methodology: Data collection was carried out by means of interviews, observation, and documentation. There were five informants in this study: Human Resource Plant Manager, People and Development Manager, Human Resource Business Partner, Labor Trainer, and Labor Trainer. Data processing was performed using the NVivo software application and source triangulation. Results: This research shows that tyre corporations that implement Balance Scorecard have succeeded in making cost improvements in their operational activities. Apart from that, innovates from a learning and growth perspective by conducting an e-learning program utilizing digital-based technology to increase the competence of its employees. The interview results show that the application of the Balance Scorecard in managing employee performance at tyre corporations using a financial perspective, customer perspective, internal business perspective, and learning and growth perspective is going very well, and by using the Balance Scorecard, success can be achieved. Cascading strategies in the area of ??human resource management have been proven to contribute to reducing human resource costs. Conclusions: The achievement indicators of the company's performance in the short term are connected to each other to achieve the predetermined vision, mission, and strategy. Limitations: The use of in-depth interviews in data collection resulted in a very limited number of informants in this study. Contribution: The use of a balance score card in employee performance analysis can help management map out strategic targets for achieving employee performance. Novelty: By cascading the company's strategy and specializing in the human resources department, it shows something new to the implementation of a balanced scorecard.